Integrated Analysis of the Effects of Cold and Dehydration on Rice Metabolites, Phytohormones, and Gene Transcripts . Issue 4 (10th February 2014) - Maruyama, Kyonoshin; Urano, Kaoru; Yoshiwara, Kyouko; Morishita, Yoshihiko; Sakurai, Nozomu; Suzuki, Hideyuki; Kojima, Mikiko; Sakakibara, Hitoshi; Shibata, Daisuke; Saito, Kazuki; Shinozaki, Kazuo; Yamaguchi-Shinozaki, Kazuko
Abstract : In cold- or dehydration-stressed rice plants, up-regulation of genes related to starch degradation, sucrose metabolism, and the glyoxylate cycle results in the accumulation of sugars and with, abscisic acid signaling is inversely related to cytokinin signaling . Abstract: Correlations between gene expression and metabolite/phytohormone levels under abiotic stress conditions have been reported for Arabidopsis ( Arabidopsis thaliana ). However, little is known about these correlations in rice ( Oryza sativa 'Nipponbare'), despite its importance as a model monocot. We performed an integrated analysis to clarify the relationships among cold- and dehydration-responsive metabolites, phytohormones, and gene transcription in rice. An integrated analysis of metabolites and gene expression indicated that several genes encoding enzymes involved in starch degradation, sucrose metabolism, and the glyoxylate cycle are up-regulated in rice plants exposed to cold or dehydration and that these changes are correlated with the accumulation of glucose (Glc), fructose, and sucrose. In particular, high expression levels of genes encoding isocitrate lyase and malate synthase in the glyoxylate cycle correlate with increased Glc levels in rice, but not in Arabidopsis, under dehydration conditions, indicating that the regulation of the glyoxylate cycle may be involved in Glc accumulation under dehydration conditions in rice but not Arabidopsis. An integrated analysis of phytohormones and gene transcripts revealed an inverse relationship between abscisic acid (ABA) signaling and cytokinin (CK) signaling under cold and dehydration stresses; these stresses increase ABA signaling and decrease CK signaling. High levels of Oryza sativa 9-cis-epoxycarotenoid dioxygenase transcripts correlate with ABA accumulation, and low levels of Cytochrome P450 ( CYP ) 735A transcripts correlate with decreased levels of a CK precursor in rice. This reduced expression of CYP735As occurs in rice but not Arabidopsis. Therefore, transcriptional regulation of CYP735As might be involved in regulating CK levels under cold and dehydration conditions in rice but not Arabidopsis.